Imaging cell spheroid clusters: An MRI protocol for non-invasive standardized characterization - Rebecca Wißmann; Petros Martirosian; Marina Danalache; Gerd Grözinger; Fritz Schick; Stefanie Elser (Heliyon)
Over the past decade, significant progress has been made in the utilization of three-dimensional cell cultures in the form of spheroids as a bridge between in vitro and in vivo models. This is contributed by natural cell-cell interactions that occur within spheroids, leading to the subsequent development of extracellular matrix. The assessment of cell spheroids with conventional microscopy is destructive, requiring sectioning that damages their micro-structures. To address these issues, we developed and propose a non-invasive approach using magnetic resonance imaging (MRI). Despite its limited spatial resolution, this method adeptly reveals information about the composition and vitality of stem cell and cancer spheroids and their micro-environment in a non-invasive manner. This work reports on the development of an MRI-compatible setup for culturing cell spheroids, tailored for use with standard 3 T whole-body MRI systems. Systematic studies with different cell types show the potential of the proposed approach for simultaneous actuation and visualization of cell spheroids, with potential across a broad spectrum of applications.